Intensi berbagi knowledge akuntansi dengan penggunaan electric communication tools berupa electric mail. instan messaging, social networking 9facebook) dan micro blogging (Twitter) - ADHA, Merelyne Rasrikotami ([Yogyakarta] : Universitas Gadjah Mada, 2010)
This research was aimed to empirically prove that technology acceptance for Electronic Communication Tools (Electronic Mail (Email), Instant Messaging, Social Networking (Facebook) and Micro Blogging (Twitter)) would affected the intention to share accounting knowledge. The basic Model for this four ECT is Heidjen (2004) modified Technology Acceptance Model (TAM). The three modified TAM constructs are consist of Perceived Usefulness, Perceived Ease Of Use and Perceived Enjoyment that has been positively predicted to affect the users intention to share accounting knowledge. The data were collected by means of 250 sets of survey questionnaires with purposive sampling method for each ECT user. The responden rate for the eligible sets for further processing are Electronic Mail (100%), Instant Messaging (98%), Facebook (96.80%) and Twitter (78%). The data analysis conducted under the Structural Equation Model (SEM) with AMOS Program Version 4.0. Findings of the research empirically proved that the four models was able to show that technology acceptance affected intention to share accounting knowledge. The Models was valid. Noted, 3 Models of ECT Email, Instant Messaging and Facebook showed significantly perceived enjoyment as one of the technology acceptance model performance indicators that can provide a more comprehensive explanation of the behavior of accounting knowledge sharing. Twitter model is the only one that does not provide empirical evidence that perceived enjoyment directly affected users intention, even so due to the simplest appearance, only the Twitter perceived ease of use significantly influenced the intention to share accounting knowledge. However in the future, it is required to specify the accounting knowledge theme so the induced behavior could clearly be showned.